September Horse. - Künstlerhaus Bethanien, Berlin (Berlin : Künstlerhaus Bethanien, 2003)
Byrne, Gerard ; Csorgo, Attila ; Dobai, Sarah ; Fishkin, Vadim ; Floricic, Alen ; Jozefowicz, Katarzyna ; Kay, Emma ; Varsó, Kis ; Lakner, Antal ; Leiderman, Yuri ; Lieber, Axel ; Putrih, Tobias ; Valuedate Net
Duits, Engels
September Horse, Künstlerhaus Bethanien Berlin, 18th September to 13th October 2002 which took place in the framework of Europe United, an initiative supported by the Culture 2000 agenda of the EU.
boek